ON SOME VECTOR VALUED GENERALIZED DIFFERENCE MODULAR SEQUENCE SPACES - Karakaya, Vatan; Dutta, Hemen (UNIV NIS, FAC SCI MATH, 2011)
In this paper we generalize the modular sequence space l{M-k} by introducing the sequence space l{M-k, p, q, s, Delta(n)((vm))}. We give various properties relevant to algebraic and topological structures of this space and derived some other spaces.
Keywords: Sequence spaces; diffrence operator; Orlicz function; paranorm; completeness; AK - BK spaces; Mathematics